Mechanical properties Investigation of Cu-SiC composites using different percentage of Magnesium element (Journal of the College of Basic Education, 2022)
The aim of this study is to produce composites of Cu –SiCp(10vol%). by using P/M method with different additions of active element like magnesium(0-10vol%) and investigating their characteristic properties.. The powders were prepared in suitable manner , blended in a ball- mill for 2 hours for good homogeneity , then pressed in uniaxial steel die with (11) mm redius to (250)MPa. The samples were sintered in electric furence to (1100°C).Density and porosity for samples were preformed. The hardness test was investigated using Vicker microhardness (HV) tester. In addition, wear resistance of specimens were also investigated by using a pin-on-disc type apparatus with a typical experimental plan of simultaneous variation of loads (5,10,15)N for (10min) .It was found that the density would be increased gradually with the Mg content. The hardness and the wear performance of the composite increased with increasing volume percentage of Mg.